Proceedings of the 3rd International Conference on Intelligent Technologies and Engineering Systems (ICITES2014) - Juang, Jengnan; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book includes the original, peer reviewed research from the 3rd International Conference on Intelligent Technologies and Engineering Systems (ICITES2014), held in December, 2014 at Cheng Shiu University in Kaohsiung, Taiwan. Topics covered include: Automation and robotics, fiber optics and laser technologies, network and communication systems, micro and nano technologies, and solar and power systems. This book also Explores emerging technologies and their application in a broad range of engineering disciplines Examines fiber optics and laser technologies Covers biomedical, electrical, industrial, and mechanical systems Discusses multimedia systems and applications, computer vision and image & video signal processing.
Active Closed-Loop Gap Control for Aerostatic Bearing -- Firefly Algorithm for Power Economic Emission Dispatch -- Application of the Taguchi Method to the War page for Light Guide Plate -- Diagnosis of Muscle Properties in Low-Back-Pain with Electrical Bio impedance Methodology -- Low Cost Wearable Control Valves with No Mechanical Sliding Parts in Valves -- Estimation of Residual Traveling Distance for Power Wheelchair Using Neural Network -- Residual Whitening Method for Identification of Induction Motor System -- Analysis and Simulation of Small-sized Quasi-servo Valve Using Tiny On/off Control Valve -- Analysis of Flexible Thin Actuator Using Gas-Liquid Phase-Change of Low Boiling Point Liquid -- Development of Flexible Pneumatic Cylinder with String Type Displacement Sensor for Flexible Spherical Actuator -- Evaluation of Computing Reliability in Internet Computing -- An Effective Method for Classification of White Rice Grains Using Various Image Processing Techniques -- Applying Zig Bee Wireless Sensors and Photovoltaic System to Plant Factory -- Applying Particle Filter Technology to Object Tracking -- Measurement of Thickness and Refractive Index of Optical Samples in FD-OCT with Two Orthogonal Polarized Lights -- Fabrication of Peristaltic Micro pump with UV Curable Adhesive -- Detecting Object Edges by Xtion Pro and Open Sources -- Temperature Control of a Baking System for an Ultra-high-vacuum Insertion Device -- Microarray Data Analysis with Support Vector Machine -- Feature Selection Algorithm for Motor Quality Types using Weighted Principal Component Analysis -- Feasibility Test of Range of Motion Exercise for Ankle Joints Rehabilitation using Pneumatic Soft Actuators -- 3D Motion Editing Through B-Spline Fitting with Constraints -- An ARAR-Tree-Based Diagnosis Mechanism for Rule Anomalies among Internet Firewalls -- Development of Active Orthosis for Lumbago Relief -- Controller Design by Time-domain Objective Functions Using Cuckoo Search -- Behavior Network-basedRisk Recognition Method -- Reinforcement Learning with Multiple Actions -- Wind Turbine Blade Load Alleviation Performance Employing Individual Pitch Control -- Planet Editing Method using Leap Motions -- Development of Flexible Haptic Robot Arm Using Flexible Pneumatic Cylinders with Backdrivability for Bilateral Control -- Integration Method of Proxy and Producer-Consumer Patterns -- Bayesian Probability and User Experience-based Smart UI Design Method -- Bayesian Probability-based Hand Property Control Method -- Implementation of a Delta-Sigma Analog-to-Digital Converter -- An Experimental Investigation of Effect on Engine Performance by Controlling the Temperature of the Fuel -- Modeling of an AIGaAs-based VCSEL with Bragg Mirrors -- Risk Decision Method based on Sensory Values of Smart Devices -- A Flywheel Energy Storage System Suspended by Active Magnetic Bearings Using a Fuzzy Control with Radial Basis Function Neural Network -- A Matrix Robot for Block-Stacking -- A Study of Regular Transmission Delay in Bluetooth Communications -- IEEE 802.16J-Based Multihop Relays for Future Performance Enhancement of Aeronautical Mobile Airport Communications Systems (AeroMACS) -- Explore the Influential Factors on Maritime Accidents by Regression Approach -- Analytical Model of Pipe Inspection Robot Using Flexible Pneumatic Cylinder -- Thermal Resistance Characterization of SIGe Based HBTs on Thick-Film and Thin-Film SOI -- Improved Item Relational Structure Theory Based on Liu's Item Ordering Consistence Property -- Enhancement of Digitized Old Film Using Inpainting Based Method -- Study of Nickel Catalysts Deposited by using the Electroless Plating Method and Growth the Multiwall Carbon Nanotubes -- Photovoltaic Power Generation System Modeling Using and Artificial Neural Network -- Thermal Stress Analysis of Layer-Wise Functionally Graded Material Beam Considering Neutral Plane -- A Smart Home Automation System -- Material Structure Selection of Solution Blue OLEDs Using a Design of Experiment -- Development of Software Inspection Tools for Defect Examination in Machine Vision Applications -- A Design of a Light Guide for Highly Uniform Illumination -- A Study on the Performance Characteristics of a Synchronous Elastic FIR Filter -- A Design of Cavity Filters based on Photonic Crystal Slab Waveguide with Liquid Crystal -- A Self-Focus High Precision Scheme Applied to HCPV Solar Center Tracker -- Controlling Flock through Normalized Radial Basis Function Interpolation -- Novel AF Relay Design for Optimizing a MIMO Relay Network under Backward Non-Flat Fading Channels -- Development of Wearable Power Assist Wear Using Pneumatic Actuators -- Cost Model of Physical Activity Monitoring Systems -- The BCI Control Applied to the Interactive Autonomous Robot with the Function of Meal Assistance -- Design of a Transparent Pipeline-Based Multiplier -- An IP-Based Design to Achieve Power Reduction -- Crystalline Indium-doped Zinc Oxide Thin Films Prepared by RF Magnetron Reactive Sputtering -- The Construction and Efficiency Validation of an Educational Module of Pneumatics Robotics Arm Controlled by Programmable Logic Controller (PLC) -- GPU Computations on Hadoop Clusters for Massive Data Processing -- A HHT Based Music Synthesizer -- Decentralized Robust Estimation of Interconnected Systems with State-Dependent Impulse Disturbances -- A Lean Analysis to Automate the Draw Operations at a Tube Manufacturing Company -- Classification of the ECG Signal using Artificial Neural Network -- Integration Method of Composite Pattern for Solving Structure Problems of Visitor Pattern -- A Circuit Design of Dimming T8 LED Tube for High Power Factor Correction -- Anti-ESD Improvement b the Bulk-Fox Structure in HV nLDMOS Devices -- N+ Extended-Distribution Influences on Anti-ESD Ability in the 60-V pLDMOS-SCR (NPN arranged-type) -- Wrist Eye: An Elderly Computer Learning Assistant with Wrist-Wearable Devices -- A Study of Ultrafast Laser-Based X-Ray Sources for In-Line Phase-Contrast Biomedical Imaging -- PC-USB-Based Real-Time Control Systems Using Quadratic Optimal Control Method -- A Bibliometric Analysis on Data Minding Using Bradford's Law.
Keywords: Telecommunication; Computer networks .; Signal processing; Communications Engineering, Networks; Computer Communication Networks; Signal, Speech and Image Processing